Prospective, randomized study of one, two, or three trabecular bypass stents in open-angle glaucoma subjects on topical hypotensive medication - Katz, L Jay (Clin Ophthalmol, 2015)
PURPOSE: To assess the safety and efficacy of one, two, or three trabecular microbypass stents in eyes with primary open-angle glaucoma (OAG) not controlled on ocular hypotensive medication. A total of 119 subjects were followed for 18 months postoperatively. MATERIALS AND METHODS: Subjects with medicated intraocular pressure (IOP) 18–30 mmHg and postmedication-washout baseline IOP 22–38 mmHg were randomized to implantation of one, two, or three stents. Ocular hypotensive medication was to be used if postoperative IOP exceeded 18 mmHg. RESULTS: A total of 38 subjects were implanted with one stent, 41 subjects with two stents, and 40 subjects with three stents. Both month 12 IOP reduction ≥20% without ocular hypotensive medication vs baseline unmedicated IOP and month 12 unmedicated IOP ≤18 mmHg were achieved by 89.2%, 90.2%, and 92.1% of one-, two-, and three-stent eyes, respectively. Furthermore, 64.9%, 85.4%, and 92.1% of the three respective groups achieved unmedicated IOP ≤15 mmHg. Over the 18-month follow-up period, medication was required in seven one-stent subjects, four two-stent subjects, and three three-stent subjects. At 18 months, mean unmedicated IOP was 15.9±0.9 mmHg in one-stent subjects, 14.1±1.0 mmHg in two-stent subjects, and 12.2±1.1 mmHg in three-stent subjects. Month 18 IOP reduction was significantly greater (P<0.001) with implantation of each additional stent, with mean differences in reduction of 1.84 mmHg (95% confidence interval 0.96–2.73) for three-stent vs two-stent groups and 1.73 mmHg (95% confidence interval 0.83–2.64) for two-stent vs one-stent groups. Adverse events through 18 months were limited to cataract progression with best-corrected visual acuity loss and subsequent cataract surgery. CONCLUSION: In this series, implantation of each additional stent resulted in significantly greater IOP reduction with reduced medication use. Titratability of stents as a sole procedure was shown to be effective and safe, with sustained effect through 18 months postoperatively in OAG not controlled with medication.